Integrating Local Science and School Science: The Benefits for Preserving Local Wisdom and Promoting Students’ Learning - Yohanes Freadyanus Kasi; Ari Widodo; Achmad Samsudin; Riandi Riandi; Novia Novia; Wati Sukmawati; Ari Syahidul Shidiq (PAEDAGOGIA, 2024)
Integrating local science into science learning benefits students and the culture. However, science teaching tends to focus only on the scientific content presented in the books but ignores the local culture. This paper explores local science in community cultural activities to be implemented in science learning to introduce students to cultural values following the concept of science. It identifies local science, describes the oral arguments produced by the tribal council, and analyzes the lesson plan by five science teachers in the Nagekeo district, East Nusa Tenggara. The data used in this analysis are observation and identification, interviews, and assessment sheets. The findings show that the local science in Nagekeo cultural activities that can be integrated into science learning includes the traditional unit and measurement systems, Newton's laws in their application to the traditional game, biodiversity in the traditional hunt, the concept of heat transfer, and its application in the construction of traditional houses, and vibrations, waves, and sounds in the traditional musical instrument. Recommendations from this research are embracing local science in science learning to provide meaningful learning for students and preserve local culture for each generation in the future so that it does not become extinct.